2008
DOI: 10.1063/1.2977967
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of the direct gas phase synthesis of H2O2 catalyzed by Au3

Abstract: The gas phase reaction of molecular oxygen and hydrogen catalyzed by a Au3cluster to yield H2O2 was investigated theoretically using second order Z-averaged perturbation theory, with the final energies obtained with the fully size extensive completely renormalized CR-CC(2,3) coupled clustertheory. The proposed reaction mechanism is initiated by adsorption and activation of O2 on the Au3cluster. Molecular hydrogen then binds to the Au3O2 global minimum without an energy barrier. The reaction between the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…According to most quantum chemical data, OOH hydrogenation is the rate-determining step in H 2 O 2 synthesis [26][27][28][29] so that OOH (s) is the main precursor. We found that an O 2 molecule from the gas phase reacts directly with H 2(s) , forming OOH (s) .…”
Section: H 2 Interaction With Pd-o 2 -Png and Au-o 2 -Pngmentioning
confidence: 99%
See 1 more Smart Citation
“…According to most quantum chemical data, OOH hydrogenation is the rate-determining step in H 2 O 2 synthesis [26][27][28][29] so that OOH (s) is the main precursor. We found that an O 2 molecule from the gas phase reacts directly with H 2(s) , forming OOH (s) .…”
Section: H 2 Interaction With Pd-o 2 -Png and Au-o 2 -Pngmentioning
confidence: 99%
“…We found that an O 2 molecule from the gas phase reacts directly with H 2(s) , forming OOH (s) . According to most quantum chemical data, OOH hydrogenation is the rate-determining step in H 2 O 2 synthesis [26][27][28][29] so that OOH (s) is the main precursor. Hence, the other reaction path is the interaction between H 2 and metal-PNG oxidized system, to obtain a molecule of hydrogen peroxide.…”
Section: H 2 Interaction With Pd-o 2 -Png and Au-o 2 -Pngmentioning
confidence: 99%
“…9 (ii) AugSBKJC(1f) corresponding to the SBKJC(1f) basis augmented by a set of s and p diffuse functions (exponent = 0.01). 46 The (spin-corrected) Z-averaged second-order perturbation theory (ZAPT) 47,48 and spherical harmonic basis functions are used together with the augSBKJC(1f) basis, while cartesian basis functions are used together with the SBKJC(1f) basis. Geometry optimisations and Hessian calculations are performed using the GAMESS-US code.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Perhaps more importantly, progress toward accurate simulations of nanowire catalysts requires addressing some fundamental issues. While small metal clusters [34][35][36][37] or embedded clusters [38] can often be treated with accurate ab initio methods, calculations on periodic nanowires or slabs are typically restricted to density functional theory (DFT) calculations using inexpensive generalized gradient approximations (GGAs) for the many-body exchange-correlation correction. [39] We [31,40,41] and others [42][43][44][45][46][47][48][49][50][51] have shown that GGAs' well-known systematic underestimate of chemical reaction barriers [52] transfer over to reactions on surfaces.…”
Section: Introductionmentioning
confidence: 99%